Social-philosophical analysis of concepts of peace and cooperation between nations - Bakhshilloyevich, Rajabov Behruz (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to provide a socio-philosophical analysis of the main concepts of peace and cooperation among nations, focusing on four perspectives: the etatist concept, the ethnological approach, racial ethnocentrism, and the transcendental dimension. It explores how moral values, human rights, and collective identity influence peaceful coexistence between diverse nations Methodology/approach: The research adopts a qualitative approach using literature-based analysis. Methods applied include synthesis, retrospective and comparative analysis, generalization, and a dialectical-synergetic framework to examine the philosophical foundations of interethnic harmony and international cooperation. Results/findings: Findings reveal that sustainable peace cannot rely solely on political agreements or legal frameworks. The etatist concept emphasizes state responsibility in ensuring equality among nations, while the ethnological approach distinguishes between natural and artificial polyethnicity. Racial ethnocentrism highlights the emotional depth of cultural identity, and the transcendental perspective underscores spiritual and moral reasoning as key drivers for long-term peace and cooperation. Conclutions: The study concludes that building lasting peace among nations requires not only treaties and institutions but also the recognition of human dignity, tolerance, and moral values as universal principles. A socio-philosophical lens enriches understanding of justice and equality in international relations. Limitations: This research is conceptual and lacks empirical testing or case-based validation of the proposed framework. Contribution: The study offers a theoretical foundation for policymakers, educators, and diplomats to foster multicultural understanding and ethical principles in promoting global peace.